The effect of training in the style of Maxex to develop the distinctive powers of speed for table tennis players - Hamaadi, Hamdullah Abed; Ibrahim, Ibrahim Khaleel (International Journal of Psychosocial Rehabilitation, 2020)
The continuous development has made the numbers recorded and the great achievements that are achieved in the game of ping-pong that soon be recorded until new numbers are achieved and so on, and all this is the result of continuous training and using the latest modern and innovative training methods and methods, and given the adoption of the sport of table tennis on two important factors (muscle strength and the art of performance) The harmony, coordination and cooperation between the different sciences was in developing muscle strength through functional and training foundations, directing this force towards technical performance with correct and economic paths, and using the muscle strength of the quadrant within kinetic pathways through which we work on the optimal investment of this strength by reducing the momentum of resistance Resulting from heaviness and increasing the force output exerted by the lifter during lifting the weight up and reducing the horizontal force component toward the vertical component of the force. The importance of training according to scientific foundations, including the reliance on building a training curriculum in the Maxex style, to develop the strength of the players’ distinctive speed and explosive ability. This is what prompted the research to enter within these variables and work to build a training curriculum in the manner of Maxex comprehensive for all these scientific variables, and to prepare a training curriculum in the manner of Maxex to develop the strength characteristic of the speed and explosive ability of players. Then, to identify the impact of the Maxex training methodology to develop the strength characteristic of the speed and explosive ability of the players. As for the research hypotheses, there are statistically significant differences between the pre and post tests among the members of the research sample for the experimental group and in favor of the post test, and there are statistically significant differences between the pre and post tests for the members of the research sample for the control group and for the post test, as well as there are statistically significant differences Between the post tests for the two research groups and for the benefit of the experimental group. The researcher used the experimental approach designed by the control and experimental groups, and the research sample included the players of Anbar club and their number (16) quadrants were divided equally into two control and experimental groups, and then the researcher conducted exploratory experiments on the research sample to find out the negatives that may accompany the main experiment, and then it was started. With field procedures for research, including pre-tests, implementation of the prepared curriculum and conducting post-tests, and after extracting the results, they were statistically processed for the purpose of analyzing and discussing them.